2011
DOI: 10.1105/tpc.111.085134
|View full text |Cite
|
Sign up to set email alerts
|

TheArabidopsisC2H2 Zinc Finger INDETERMINATE DOMAIN1/ENHYDROUS Promotes the Transition to Germination by Regulating Light and Hormonal Signaling during Seed Maturation

Abstract: Seed development ends with a maturation phase that imparts desiccation tolerance, nutrient reserves, and dormancy degree. Here, we report the functional analysis of an Arabidopsis thaliana C2H2 zinc finger protein INDETERMINATE DOMAIN1 (IDD1)/ENHYDROUS (ENY). Ectopic expression of IDD1/ENY (2x35S:ENY) disrupted seed development, delaying endosperm depletion and testa senescence, resulting in an abbreviated maturation program. Consequently, mature 2x35S: ENY seeds had increased endosperm-specific fatty acids, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(90 citation statements)
references
References 126 publications
2
88
0
Order By: Relevance
“…Meanwhile, GA relieves the repression of the DELLAs by promoting their degradation via the 26S proteasome pathway. More recently, DELLAs have been shown to interact with and inhibit the activity of numerous transcription regulators (Cheminant et al, 2011;Feurtado et al, 2011;Josse et al, 2011;Hong et al, 2012;An et al, 2012;Zhang et al, 2011). By doing so, GA signaling controls the expression of a multitude of target genes functioning in distinct pathways.…”
Section: Development At a Glancementioning
confidence: 99%
“…Meanwhile, GA relieves the repression of the DELLAs by promoting their degradation via the 26S proteasome pathway. More recently, DELLAs have been shown to interact with and inhibit the activity of numerous transcription regulators (Cheminant et al, 2011;Feurtado et al, 2011;Josse et al, 2011;Hong et al, 2012;An et al, 2012;Zhang et al, 2011). By doing so, GA signaling controls the expression of a multitude of target genes functioning in distinct pathways.…”
Section: Development At a Glancementioning
confidence: 99%
“…RA1 and KN1 co-occupied the same site in the promoter of another IDD gene, an ortholog of LOOSE PLANT ARCHITECTURE 1, which regulates tiller angle in rice ), but loss of kn1 function did not alter its expression. RA1 (Feurtado et al 2011). Evidence for combinatorial action of IDD genes in developmental patterning has recently emerged (Welch et al 2007;Reinhart et al 2013;Slewinski 2013), including novel roles in lateral organ development via regulation of auxin biosynthesis and transport (Cui et al 2013).…”
Section: Common Targets Of Ra1 and Knotted1 Link Meristem Determinacymentioning
confidence: 99%
“…These interactions integrate GA with various signals for coordinated regulation of plant growth and defense (Hou et al, 2010;Bai et al, 2012). Although studies of recently identified DELLA-interacting proteins have revealed the mechanisms of several GA-mediated responses (Arnaud et al, 2010;Cheminant et al, 2011;Feurtado et al, 2011;Yu et al, 2012;MarĂ­n-de la Rosa et al, 2014), much work is required to obtain a clear understanding of the numerous roles played by GA.…”
Section: Introductionmentioning
confidence: 99%